Manajemen Sumber Daya Manusia Di Puskesmas Polongbangkeng Utara Kabupaten Takalar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This research aims to determine the description of Human Resources Management at the North Polongbangkeng Community Health Center, Takalar Regency. This type of research uses a qualitative approach. The data collection technique was carried out using triangulation, the data processed tended to be qualitative data, data analysis was inductive/qualitative. The results of the research showed that the implementation of Human Resource Management had been carried out well at the North Polongbangkeng Community Health Center, Takalar Regency through selection, assessment, compensation and development indicators. Regarding the selection process where employees are selected carefully in accordance with the selection criteria that have been determined in government policies/regulations. with employee performance appraisals where employees who have good competencies and skills and include related documents will also have an influence on their performance achievements.